Analisis time series hubungan variabilitas iklim dan produktivitas padi dalam upaya mendukung ketahanan pangan: Studi kasus Kabupaten Bogor periode 2020-2024 - Fananda Putri M NOH; Melati Janet Livia Simanjuntak (Papanda Publisher, 2026)
Rice production in Bogor Regency plays an important role in supporting regional food security. During the 2020–2024 period, rice production fluctuated between approximately 283,000–300,000 tons per year, while harvested area ranged from about 50,000–57,000 hectares. This study aims to analyze climate variability trends—rainfall, average air temperature, and relative humidity—and examine their relationship with rice production and productivity in Bogor Regency. A quantitative time series approach was applied using seasonal decomposition, the Mann–Kendall trend test, Pearson correlation, and simple linear regression. The results show that rainfall decreased by –0.5 mm/year, relative humidity decreased by –0.62%/year, and temperature increased by 0.145°C/year. The Mann–Kendall test confirms that all climate variables exhibit statistically significant trends (p < 0.05). Rice production shows a downward trend with a slope of –48.4 tons/year, while harvested area declines more sharply at –1,747.45 ha/year. However, correlation and regression analyses indicate that rainfall, temperature, and humidity do not have a statistically significant direct effect on rice production or productivity (p > 0.05). The decline in rice production is more strongly associated with the reduction in harvested area than with short-term climate variability. These findings suggest that climate variability plays an indirect role, while structural factors such as land-use change are more dominant in influencing rice production dynamics. The results provide evidence-based input for regional agricultural planning and land protection policies to support sustainable food security.